Dynamics of surfaces and reaction kinetics in heterogeneous catalysis : proceedings of the international symposium, Antwerp, Belgium, September 15-17, 1997 - Froment, Gilbert F.; Waugh, K. C. (Studies in surface science and catalysis, 1997)
Many processes of the chemical industry are based upon heterogeneous catalysis. Two important items of these processes are the development of the catalyst itself and the design and optimization of the reactor. Both aspects would benefit from rigorous and accurate kinetic modeling, based upon information on the working catalyst gained from classical steady state experimentation, but also from studies using surface science techniques, from quantum chemical calculations providing more insight into possible reaction pathways and from transient experimentation dealing with reactions and reactors. This information is seldom combined into a kinetic model and into a quantitative description of the process. Generally the catalytic aspects are dealt with by chemists and by physicists, while the chemical engineers are called upon for mechanical aspects of the reactor design and its control. The symposium "Dynamics of Surfaces and Reaction Kinetics in Heterogeneous Catalysis" aims at illustrating a more global and concerted approach through a number of prestigious keynote lectures and severely screened oral and poster presentations.